2000
DOI: 10.5860/crl.61.5.432
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring a Liaison Program in an Academic Library

Abstract: New technologies, an expanding universe of knowledge, and a more sophisticated user base influence not only how we provide access to information, but also how we define and organize ourselves in relation to the public. The J. Murrey Atkins Library of the University of North Carolina at Charlotte has endeavored to strengthen the relationship between the library and the teaching faculty by restructuring the library's liaison program. Concurrently, but independent of this redesign, three experienced reference lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
4
1
Order By: Relevance
“…31 Our survey of faculty generally confirms the results of previous studies in that faculty who have more contact with or received more services from their liaison are more satisfied with the liaison than those who have less. 32 In our survey, more recent contact with the librarian was not associated with greater satisfaction with the library overall, unlike what had been found in a study at nine New England colleges. 33 Challenges for liaisons that have been documented in previous surveys also were confirmed in this survey.…”
Section: Relationship Of Results To Previous Studiescontrasting
confidence: 84%
“…31 Our survey of faculty generally confirms the results of previous studies in that faculty who have more contact with or received more services from their liaison are more satisfied with the liaison than those who have less. 32 In our survey, more recent contact with the librarian was not associated with greater satisfaction with the library overall, unlike what had been found in a study at nine New England colleges. 33 Challenges for liaisons that have been documented in previous surveys also were confirmed in this survey.…”
Section: Relationship Of Results To Previous Studiescontrasting
confidence: 84%
“…Mozenter, Sanders, and Welch's (2000) survey of teaching faculty in ten departments at UNC Charlotte evaluated the implementation of a restructured liaison program. The authors concluded that the program needed to be re-evaluated regularly, and that "the survey seemed to support the thesis that proactive liaisonship provides the greatest satisfaction" (p. 439).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a lack of research exploring possible links between ILL usage and librarian liaison work. Mozenter et al (2000) explores the restructuring of liaison services at one university library. Although the author successfully addresses the challenges and diversity of assessing and restructuring a liaison program the link between ILL and liaisons is absent.…”
Section: Literature Reviewmentioning
confidence: 99%